Securitisation and its Footprint: The Rise of the U.S. Securities Industry Centres 1998-2007. - Wójcik, D (School of Geography and Environment (University of Oxford), 2009)
This paper conceptualises securitisation from an economic geographic perspective, and documents dynamic but volatile growth of the securities industry and its distribution in the U.S.A. between 1998 and 2007. The industry has spread across states and metropolitan areas, within which it has enhanced its position in central districts, crowding out credit and insurance industry. Corporate headquarters have become more concentrated and their distribution has become more similar to the location of the securities industry centres. The results have implications for a revision of the global city theory, and corroborate research on the geography of stock markets and financialisation.